Apical Dominance in Plants and its remedial technique - Lal, Shanker; Pal, Madan; Kumar, Arun (Indian Farming, 2017)
Practicality and wisdom shows the way to improve/enhance the quantity of product in plants. Removing apical dominace in some plants has shown to enhance the vegetative growth and vigorous fruiting in certain group of plants.